The determinants and profitability of currency carry trade during periods of market turmoil - Bouakicha, Celia (2020)
This dissertation is an empirical analysis of the determinants of currency carry trade. This study examines the yields engendered by this carry trade strategy during different periods of time with a focus on financial market turmoil periods. It also investigates the connections between carry trade returns and volatility. The currency carry trade is defined by borrowing low-interest-rate currencies and investing the proceeds in high-interest-rate currencies. Investors receive the yield differential in the absence of movements in the exchange rate level. The studied sample is constituted of the spot and forward exchange rate of the developed economies currencies from 1990 to 2020. The currencies were ranked into five different portfolios according to their interest rate differential. Portfolios were ranked from lowest to highest interest rates to examine the profitability. We ﬁnd that carry trade is a profitable investment strategy with annual excess returns of 3.78% and a Sharpe ratio of 0.49, even after accounting for market turmoil. However, during the peak of the financial crisis, our portfolios mimicking typical carry trade investments, suffered losses of about 30% on their invested capital, suggesting a time variation in the profitability of carry trade strategy. Thus, this dissertation substantiates that in time of market turmoil, carry trade underperforms and its lowest-interest-rate currencies offer a hedge by producing positive returns while the highest-interest-rate currencies co-move negatively with volatility and therefore generate low returns. Although carry trade has led to significant losses in times of market turmoil, its losses are relatively minor, compared to its overall historic returns.